Governance capacity, state policy and the rise of the Chongqing notebook computer cluster. Issue 3 (3rd July 2019) - Gao, Boyang; Dunford, Michael; Norcliffe, Glen; Liu, Weidong
ABSTRACT: The ability of a local development-oriented state to make their localities nodes in global production networks (GPNs) depends on the policy instruments available to it and the capacity of various actors to exploit this policy envelope fully and effectively. The post-2008 relocation and expansion in Chongqing of a coastal Chinese notebook computer manufacturing cluster is a compelling example of an activist state relocating and expanding parts of a GPN, and exporting globally from an inland location. Functional roles and governance capacity are examined through a study of the ways in which the Chongqing Municipal Government drew on government–industry relations, economic infrastructure, and social overhead capital provision, labour market organization and preferential policies, including measures to support chain logistics in and after industrial transfer, to couple its ambitions of lead companies, original equipment manufacturers (OEMs) and local enterprises with its own strategic goals.